The Paleo-Orientations of Northwestern Borneo and Adjacent South China Sea Basins - H. D. Tjia (Geological Agency, 2012)
DOI: 10.17014/ijog.v7i2.136Limited paleomagnetic data from West Kalimantan and southwestern Sarawak appear to indicate counter-clockwise (CCW) rotation of over 50 degrees during Cenozoic. On the other hand, similar studies from Sabah show conflicting results in terms of paleo-positions. This CCW information and other plate tectonic considerations have formed the base of Southeast Asia’s plate reconstructions that have seen print in a number of updated versions. The existing publications on extensive field and exploration data, including geological stress fields from wellbore breakouts, on northwestern Borneo and basins of South China Sea have not been taken into account. The latter wealth of information already established that the region under discussion consists of a mosaic-like assemblage of diverse tectono-stratigraphic terranes, each with separate tectonic development. Stress fields changed in different ways in the different terranes indicating definitively that regional, progressive CCW rotation of Borneo is not possible.